2016
DOI: 10.1155/2016/9416054
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Urinary Metabolites of Organophosphate Flame Retardants, TDCIPP, and TPHP, in Pregnant Women in Shanghai

Abstract: Flame retardants are widely used in consumer products to reduce their flammability. Previously used flame retardants have been sequentially banned due to their environmental and human toxicity. Currently, tris(1,3-dichloropropyl) phosphate (TDCIPP) and triphenyl phosphate (TPHP) are among the most commonly used flame retardants. TDCIPP and TPHP are reproductive toxins and have carcinogenic, neurotoxic, and endocrine-disrupting properties. Although high levels of TDCIPP and TPHP have been found in drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
(57 reference statements)
7
23
1
Order By: Relevance
“…Exposure levels in our study population were similar to those reported in the literature for general population exposure with GM concentrations of the PFR metabolites similar to other adult populations in China (Feng et al 2016), Norway (Cequier et al 2015), and the U.S. considering that differences in the timing of sample collection and population size complicate such comparisons (Butt et al 2014; Butt et al 2016; Carignan et al 2013b; Castorina et al 2017; Cooper et al 2011; Dodson et al 2014; Kate Hoffman et al 2017; Hoffman et al 2015; Preston et al 2017; Romano et al 2017) (Supplemental Material Table S4). Concentrations of BDCIPP and DPHP among men in our study population were approximately 2 fold and 90% higher, respectively, than previously measured among a population of 45 men recruited from the Vincent Memorial Andrology laboratory at Massachusetts General Hospital in 2002–2007 (Meeker et al 2013a).…”
Section: Discussionsupporting
confidence: 88%
“…Exposure levels in our study population were similar to those reported in the literature for general population exposure with GM concentrations of the PFR metabolites similar to other adult populations in China (Feng et al 2016), Norway (Cequier et al 2015), and the U.S. considering that differences in the timing of sample collection and population size complicate such comparisons (Butt et al 2014; Butt et al 2016; Carignan et al 2013b; Castorina et al 2017; Cooper et al 2011; Dodson et al 2014; Kate Hoffman et al 2017; Hoffman et al 2015; Preston et al 2017; Romano et al 2017) (Supplemental Material Table S4). Concentrations of BDCIPP and DPHP among men in our study population were approximately 2 fold and 90% higher, respectively, than previously measured among a population of 45 men recruited from the Vincent Memorial Andrology laboratory at Massachusetts General Hospital in 2002–2007 (Meeker et al 2013a).…”
Section: Discussionsupporting
confidence: 88%
“…Due to limited studies characterizing PFRs in male cohorts, we are unable to conclude the PFR concentrations found in our study do not reflect levels in the general population or that men from a fertility clinic would respond differently to PFR exposure. Concentrations of PFRs in our sample are similar to those measured among the female partners of the EARTH study cohort (Carignan et al , 2017), yet considerably lower compared to more recent samples of pregnant women in Durham, North Carolina (Hoffman et al , 2017b) and Shanghai, Chania (Feng et al , 2016). Contrary to PBDEs which have a long half-life, PFRs are less-persistent and samples are subject to exposure misclassification since urinary metabolite levels may reflect exposure only hours or days prior to sample collection.…”
Section: Discussionsupporting
confidence: 69%
“…Recent biomonitoring studies have demonstrated that exposures are ubiquitous among U.S. adults [ 34 36 ]. Individual characteristics predictive of higher exposures to PFRs are not well-established, and the previous biomonitoring studies have focused primarily on pregnant women and mother-child pairs [ 35 , 37 40 ]. Further elucidation of determinants of increased exposures to PFRs and the mechanisms underlying observed variability across individuals are important for potential exposure mitigation efforts and for interpreting biological monitoring data in epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%